Affirmer son identité à travers la mise en scène de la nourriture dans les médias socionumériques : l’exemple d’influenceuses culinaires musulmanes - Mohamed Sakho Jimbira; Dimitri Almeida (Communiquer)
Drawing from a methodological approach that combines nethography and discourse analysis, the article proposes a reflection on the practices of hijabi influencers who produce digital culinary contents on social media. The article highlights the ways in which four hijabi influencers, Baraa Bolaat, NailaHijab, Asma Fares and Underrated Hijabi, who work in socio-cultural environments where Islam is a minority religion, engage in practices of self-representation and develop narratives through what they eat or cook. The analysis shows that these practices can be understood as a form of empowerment that takes at least two forms: first, that of a visuality and agency through which hijabi influencers forge their own media space, as well as a desire to blur the boundaries between the domestic sphere and public space.